BUDAYA ORGANISASI DAN PENDIDIKAN (Studi Budaya Militer dan Budaya Akademik di Akademi TNI Angkatan Laut Surabaya) - Simanullang, Sihar (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
According to Rosene (2005) the challenge ahead for naval organization will need a futuristicleader that are inspiring, initiative, innovative, have commitment and trust to deal with thephenomenon of asymmetric warfare in the 21st century. Complexity of these challengesrequires the expertise of naval soldiers who are capable of leading change, leading people andstewarding resources. In response to the problem, Indonesian Naval Academy is supposed toreform itself to reevaluate with its function as a naval educational institution. One of thecharacteristics of military educational institutions is its culture that is directed to the buildingof military character as the major component in defense duty and also become the factor thatdistinguishes it to the other components. Therefore, AAL as the military educationalinstitution which educate prospective Indonesian navy officers, has to make organizationalculture itself as one of the aspect of the education development. The purpose of awardingacademic degrees to AAL graduates is as a hope for a better life. Hoping better especially inacademic field is something logical and rational for educational institution like AAL.Therefore, in order to achieve academic goals as stated in the vision and mission of AAL,academic culture should be transformed and developed in AAL education. The aims of thisresearch are to describe and analyze the organizational culture of the Indonesian NavalAcademy(AAL), and examine of how the transformation of academic culture in theIndonesian Naval Academy education. The research is focused on organizational culturewhich underlying the behavior of cadets relates to academic culture that develops in AALeducational institutions. The technique of data analysis in this research uses qualitativeresearch approach. Based on these research result, it is found that the organizational culture inAAL is still likely to retain the old culture. The old culture that is filled with a strong militaryculture still dominates the life system in AAL, so that it becomes one of the factors that leadto academic culture to thrive. It needs a cultural leader to be able to make a cultural change tobe better in Indonesian Naval Academy.Keywords : Organizational Culture, Academic Culture Transformation